2010
DOI: 10.4162/nrp.2010.4.4.323
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nutrient intake, life style variables, and pregnancy outcomes by the depression degree of pregnant women

Abstract: The aim of this study was to analyse effects that the degree of depression have on the life style variables, nutrient intake, iron indices and pregnancy outcome. Subjects were 114 pregnant women who were receiving prenatal care at a hospital in Seoul. We collected data for general characteristics and lifestyle variables from general survey instrument and for depression score from the questionnaire on depression. Dietary intakes of subjects were estimated by 24 hour dietary recall method. Also we analysed iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 14 publications
6
28
1
Order By: Relevance
“…Regarding calcium intake, our results are in partial agreement with those of the aforementioned Korean study, in which calcium intake was significantly higher in the group scoring low for depression than in the group scoring high for depression. 7 Another cross-sectional study of 105 Korean women aged 41-57 years showed a significant inverse association between calcium intake and selfrated depression. 8 This finding is also in partial agreement with the current results.…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding calcium intake, our results are in partial agreement with those of the aforementioned Korean study, in which calcium intake was significantly higher in the group scoring low for depression than in the group scoring high for depression. 7 Another cross-sectional study of 105 Korean women aged 41-57 years showed a significant inverse association between calcium intake and selfrated depression. 8 This finding is also in partial agreement with the current results.…”
Section: Main Findingsmentioning
confidence: 99%
“…2 The possible role of dairy products and calcium in depressive symptoms has received much less attention; moreover, the findings have been inconsistent. [3][4][5][6][7][8] In Japan, calcium intake during pregnancy is below not only the recommended intake levels for Japan but also the average intake levels in other developed countries. 9 To our knowledge, only one epidemiological study has addressed the association between calcium intake and depressive symptoms during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prenatal depression has been associated with LBW (17,19,20). However, contradicting findings have also been reported (21)(22)(23)(24)(25), possibly due to differences in study methodology and design (e.g. different psychometric tools, diverse study samples).…”
Section: Introductionmentioning
confidence: 56%
“…Anxiety symptoms during pregnancy have been reported to be associated with LBW in several studies (16,17,26), while others have not confirmed this association (22,23,(27)(28)(29). A number of studies indicate an association between low Apgar score of the newborn and prenatal depression and anxiety (9,22), while, in other studies, this association does not exist (22,24,25).…”
Section: Introductionmentioning
confidence: 76%